2018
DOI: 10.1002/pd.5325
|View full text |Cite
|
Sign up to set email alerts
|

Rare autosomal trisomies: Important and not so rare

Abstract: Rare autosomal trisomies are not rare and often associated with poor obstetric outcomes. They should be discussed with the clinician to guide management. Pregnancy outcomes varied by chromosome being generally favourable for some (eg, trisomy 7) and poor for others (eg, trisomy 22). In the presence of a RAT, pregnancy-associated plasma protein-A is predictive of placental dysfunction and fetal growth restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
55
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 18 publications
(34 reference statements)
10
55
1
1
Order By: Relevance
“…One of the main study limitations was that this was a selected set of pregnancy samples and thus may not be truly representative of a larger general pregnancy population. Other recent publications have looked at genome-wide NIPT in patient populations of at least 10,000 patients [5,6,34,43], with a few publications reporting results from populations of over 50,000 patients [28,44,45]. However, the observed assay failure rate and FF distribution in our study population were consistent with those observed in the referral population, suggesting the data is representative.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…One of the main study limitations was that this was a selected set of pregnancy samples and thus may not be truly representative of a larger general pregnancy population. Other recent publications have looked at genome-wide NIPT in patient populations of at least 10,000 patients [5,6,34,43], with a few publications reporting results from populations of over 50,000 patients [28,44,45]. However, the observed assay failure rate and FF distribution in our study population were consistent with those observed in the referral population, suggesting the data is representative.…”
Section: Discussionsupporting
confidence: 82%
“…In France, these ACAs account for 12.25% of all prenatal unbalanced chromosomal abnormalities and 2.5% of all prenatal karyotypes [31]. These ACAs have been shown to be associated with a poor prognosis, including miscarriage, intrauterine fetal death, intellectual development disorders, and malformative syndromes [29,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…This was then expanded to include optional testing for fetal sex and sex chromosome aneuploidies [12,13], and later to include the option of screening for common microdeletions [14,15], rare autosomal aneuploidies, and partial deletions and duplications [16][17][18]. The additional fetal anomalies that are captured following genome-wide testing can impact patient management as they are often associated with serious pregnancy complications [16,19]. The ability of commercially available NIPT assays to detect additional fetal anomalies is dependent on the technology used by the assay.…”
Section: Introductionmentioning
confidence: 99%
“…NIPT can evaluate chromosomes other than 13, 18, 21, X and Y. Rare autosomal trisomy (RAT) can have sometimes adverse effects on pregnancy outcomes [10,11]. The most common RAT detected in NIPT involved chromosome 7 and 16 [12].…”
Section: Introductionmentioning
confidence: 99%